Design and development of UrbanConcept car - Rahman, Mohammed Ataur (2010)
The “UrbanConcept” vehicle is defined as a fuel economy pure electrical vehicle which will be the closer in appearance and technology to road-going vehicles, addressing current transportation. Increasing the fuel shortage and hiking the fuel price are made the political un-stability all over the world year-toyear and decade-to-decade. While, the automotive exhaust gas emission has a significant impact on environment. This is problem and big one at this moment. For decades scientists and politicians have struggled with finding solutions to these important problems. From this study it is committed to offer a most fuel-efficient vehicle and to reduce the environmental footprint of its operations and to help meet the world’s growing demand for energy in secure and sustainable ways. To design and build this vehicle is the most challenging to make the vehicle weight below than 200 kg (including 70 kg driver weight). The goal of the project is not to operate with high speed but emphasis is given on the consumption as little fuel as possible over a set distance. Theoretically, it is found that the developed vehicle that travel further using less energy will achieve 1820 km per 1 litre equivalent of fuel. Furthermore, the design and developed vehicle will not only to contribute to the fuel efficiency vehicle, but also incorporate recycled and eco-friendly materials into the vehicle. One particular feature of this vehicle is that the waste power from the braking will be recover from regenerative braking system as the vehicle will follow-up “stop & go” driving. The vehicle will be propelled from the power of hub traction motor which will powered by super capacitor.